The Gambia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2000)
The note views the problem of poverty in The Gambia. The largest group of cash crop producers have the highest poverty rate in the country. The design of public policies in the area of education and health has a large impact on the living standards of the poor. Therefore, these social policies have to be supported by policies that enhance the poor households' access and use of formal financial services. The note discusses the Gambian government's attempts to address the growing incidence of poverty.